Thank you for registering.

One of our academic counsellors will contact you within 1 working day.

Please check your email for login details.
MY CART (5)

Use Coupon: CART20 and get 20% off on all online Study Material

ITEM
DETAILS
MRP
DISCOUNT
FINAL PRICE
Total Price: Rs.

There are no items in this cart.
Continue Shopping

6x-9-2(1+x)=x-9 6x-9-2(1+x)=x-9 6x-9-2(1+x)=x-9 6x-9-2(1+x)=x-9

6x-9-2(1+x)=x-9
 
6x-9-2(1+x)=x-9
 
6x-9-2(1+x)=x-9
 
6x-9-2(1+x)=x-9

Grade:12

1 Answers

Harshit Singh
askIITians Faculty 5964 Points
9 months ago
Dear Student

2(x+2)+5(x+5) = 4(x-8)+2(x-2)

2x + 4 + 5x + 25 = 4x – 32 + 2x – 4

2x + 5x -4x – 2x = -32 – 4 -4 – 25

7x – 6x = -65

x = – 65

Thanks

Think You Can Provide A Better Answer ?

Provide a better Answer & Earn Cool Goodies See our forum point policy

ASK QUESTION

Get your questions answered by the expert for free